Keterampilan Dan Etika Komunikasi Islami Antarpribadi Di Dalam Buku Enjoy Your Life Karya Dr. Muhammad Al-Areifi - m. Toha (UIN Antasari Banjarmasin, 2017)
The ability to communicate interpersonally is a very important skill for anyone. This is because everyone needs to establish a harmonious relationship with other fellow human beings. However, the fact that communication is not something that is easy. Therefore, we must do various efforts to improve our communication skills. in addition we must also study the ethics of communication as our basic principle in communicating. one of the best sources of communication skills is the Qur'an and Sunnah of Prophet Muhammad s.a.w. One of the books that the authors assume summarizes the skills and ethics of interpersonal communication is Dr. Enjoy Your Life's book. Muhammad Al Areifi. Departing from these assumptions, the authors decided to conduct in-depth research on the book using qualitative content analysis methods and it was answered that the book is indeed loaded with a summary of skills and communication ethics according to the Qur'an and sunnah. Among the results of the study on Enjoy Your Life the author found 11 skill subcategories with 290 skill points and 7 categories of ethics with 111 ethical points. From the research the writer can conclude that there are many skills and ethics of interpersonal Islamic communication that can make us good communicator